OCCUPATIONAL/CAREER INDECISION FOR ECONOMICALLY DISADVANTAGED HIGH SCHOOL STUDENTS OF HIGH INTELLECTUAL ABILITY: A MIXED‐METHODS COGNITIVE PROCESS MODEL. Issue 7 (24th April 2017) - Jung, Jae Yup; Young, Marie
Abstract : A mixed‐methods design was employed to identify the cognitive processes that lead to occupational/career indecision for economically disadvantaged adolescents of high intellectual ability. In the first phase, interview data collected from 26 economically disadvantaged intellectually gifted Australian adolescents were analyzed using grounded theory to develop two alternative models of cognitive processes that lead to occupational/career indecision. In the second phase, these models were quantitatively tested and refined using structural equation modeling of survey data collected from 917 economically disadvantaged intellectually gifted Australian adolescents. The finally accepted model, identified using a competing models strategy, suggested that valuing the thoughts of family on general matters is positively predictive of a desire to live up to one's potential and the experience of amotivation about the occupational decision. In turn, occupational amotivation appears to be positively associated with occupational indecision, but negatively associated with multipotentiality and a desire to fulfill one's potential.